Genes and Environment - Kawanishi, Masanobu; Yagi, Takashi
Genes and Environment is an open access, peer-reviewed journal that aims to accelerate communications among global scientists working in the field of genes and environment. The journal publishes articles across a broad range of topics including environmental mutagenesis and carcinogenesis, environmental genomics and epigenetics, molecular epidemiology, genetic toxicology and regulatory sciences.